PELAKSANAAN STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK TANGGUNG JAWAB AKADEMIK SISWA (Studi Kasus Kelas 1 SDIT Ar Rahman Petukangan Jakarta Selatan) - Yanti Oktaviani; Busahdiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the phenomenon of students who often show undisciplined behavior in the learning process, such as rushing to complete assignments due to peer influence, lack of focus, and leaving tasks unfinished. This phenomenon indicates problems in students' academic attitudes that have not been optimal. This study aims to analyze the strategies of Islamic Religious Education teachers in forming the academic responsibility of first-grade students at SDIT Ar Rahman Petukangan, South Jakarta. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of Islamic Religious Education teachers as the main informants, as well as first-grade students and the principal as supporting informants. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The validity of the data was strengthened by triangulation techniques. The results showed that: 1) Islamic Religious Education teachers apply various strategies in forming students' academic responsibility, including group formation and point systems, habituation of discipline and responsibility, teacher exemplary, and integration of Islamic values in every learning process; 2) The results of these strategies can be seen from the increased focus of students in learning, seriousness in completing assignments, and compliance with class rules, although these impacts have not been evenly distributed among all students; 3) Obstacles faced include the characteristics of lower-grade students who are still easily influenced by peers, lack of patience, and the influence of the family environment. The solutions implemented are individual approaches, continuous reinforcement, and establishing collaboration with homeroom teachers and parents.